Keurbooms Estuary floods and sedimentation - Schumann, Eckart H. (South African Journal of Science, 2015)
The Keurbooms Estuary at Plettenberg Bay lies on a wave-dominated, microtidal coast. It has a dune-topped sandy barrier, or barrier dune, almost 4 km long, with a narrow back-barrier lagoon connected to its source rivers, the Keurbooms and Bitou. The estuary exits to the sea through this barrier dune, and it is the geomorphology and mouth position in relation to floods, which is the subject of this paper. Measurements of rainfall, water level, waves and high- and low-tide water lines were used to analyse the mouth variability over the years 2006–2012. Two major floods occurred during this time, with the first in November 2007 eroding away more than 500 000 m3 of sediment. The new mouth was established at the Lookout Rocks limit – the first time since 1915. The second flood occurred in July 2012 and opened up a new mouth about 1 km to the north-east; high waves also affected the position of the breach. The mouth has a tendency to migrate southwards against the longshore drift, but at any stage this movement can be augmented or reversed. The effectiveness of floods in breaching a new mouth through the barrier dune depends on the flood size and the nature of the exit channel in the back-barrier lagoon. Other factors such as ocean waves, sea level, vegetative state of the dune and duration of the flood are also important and can determine where the breach occurs, and if the new mouth will dominate the old mouth.